Fostering emotional well-being in adolescents: the role of physical activity, emotional intelligence, and interpersonal forgiveness - Yang, Shicheng; Jing, Longjun; He, Qianqian; Wang, Huilin (Frontiers in Psychology, 2024)
Adolescence is considered a stress-sensitive developmental period, and the escalating and sustained pressure during this phase poses a significant threat to the mental and physical wellbeing of adolescents. Therefore, enhancing positive emotions in adolescents is crucial. This study aims to investigate the impact of physical activity on the emotional intelligence, interpersonal forgiveness, and positive emotions of adolescents.Methods: Using a cluster sampling method, data were collected from 500 adolescents in four schools across the Xiangxi Tujia and Miao Autonomous Prefecture of Hunan Province, China. A total of 428 valid questionnaires were collected and analyzed. The study employed AMOS v.23 to construct a structural equation model to validate the hypotheses.The results indicate that physical activity significantly influences the emotional intelligence, interpersonal forgiveness, and positive emotions of adolescents. Furthermore, emotional intelligence and interpersonal forgiveness mediate the relationship between physical activity and positive emotions.Discussion: Based on these findings, collaborative efforts from government agencies, schools, and families are essential to provide robust support for adolescents' participation in physical activity, encouraging more adolescents to actively engage in sports.